Food industries in the sultanate of Oman: reality and development mechanism from the point view of decision makers in private sectors (Damascus University Journal for the economic and Political sciences, 2024)
The study aimed at investigating Omani food industries’ reality and development mechanism from the point view of decision makers in private sectors. To achieve the purpose of the study a questionnaire consisted of 34 items distributed into 6 dimensions was used to collect data from 70 decision makers. The results showed that Omani food industries lack a road map for their development. It also indicated that there are a number of factors contribute to distribution of the industries among difference sectors. It also showed that the production capacity of these industries does not cover the demand of the market despite of the possibility of increasing production. It also revealed that these industries face several challenges such competition, labor costs, lack of technology and raw materials. The study also showed the need for opening new markets to import raw materials and providing ski full labor, enhancement of technology application and quality of the products.
Keywords: Food Industries; Reality; Development Mechanism; Decision Makers; Oman